Evaluation Status Of Central Laboratories In Al- Kadhimya Teaching Hospital According To ISO/IEC 17025 In 2005 - العبادي سناء عبد الرحيم; هاشم بشرى حسن (Journal of Economics and Administrative Sciences, 2025)
This research aims to analyze and evaluate the reality of the total quality management for the central laboratories by comparing systems of work in the laboratories of Al- Kadhimiya Didactic Hospital with the requirements of ISO 17025 to determine the degree of compatibility and the willingness to adapt to the requirements of the above specification and to show the ability of building an applicable quality management system and to identify problems and their mitigations and prevention to increase. This study gains its importance from the importance of the labs which stems from the fact that the process of health is a set of interrelated activities, Medical examinations and tests constitute one of the fundamental pillars through correct diagnosis of the health situation and careful follow-up of patients as well as the importance of examining the problems encountered in the performance of medical laboratories, which are a constraint to the achievement of the main goals of the laboratories. The research arrived to the conclusions, that the achievement of the quality of the performance which is a dream of all organizations regardless of whether it belongs to the government sector, or to the private sector, means achieving existence, and consistent quality means the continuation of existence, and to strengthen quality means to strengthen presence. Reliance is a means to achieve quality assurance as a process of continuous assessment and to obtain a certificate of reliability in the laboratory will be applied ISO 17025 with the methods and contexts for quality control. The research concludes with a set of recommendations, one of the most important is building bridges of coordination with the Ministry of Health to adopt standards of quality and reliability to keep pace with progress in this area and to form a higher committee for quality and reliability in the health sector joining the Ministry of Health’s authority and coordination with professional associations such as the Union of doctors, dentists , pharmacists, etc., in addition to the involvement of the Central Agency for Standardization and Quality Control as the representative of the Iraqi State in the International Organization for Standardization to strengthen the oversight role and application of the standards in the laboratory by developing a separate unit, trained and with specific tasks.